Dynamic response of a segmented tunnel in saturated soil using a 2.5-D FE-BE methodology. Issue 120 (May 2019) - Zhou, Shunhua; He, Chao; Guo, Peijun; Yu, Fan
Abstract: The majority of existing subway tunnel lines are constructed by the shield method, which is assembled by several segmental linings connected by joints. However, the previous studies on the prediction of vibrations from underground railways mostly considered the tunnel as a closed homogeneous ring. This paper proposed a two-and-a-half-dimensional (2.5-D) finite element-boundary element (FE-BE) methodology to investigate the dynamic response of a segmented tunnel in the saturated soil. The segmental linings and connecting joints are simulated as 3-D isotropic elastic solids and a set of springs by the 2.5-D FE method, respectively. The surrounding soil is modelled by the 2.5-D BE method for a saturated porous medium. The 2.5-D FE method and the 2.5-D BE method are then coupled via the boundary conditions on the tunnel–soil interface. Numerical results show that a homogeneous tunnel model underestimates the dynamic stress and pore-water pressure in the foundation soil. The influence of the tunnel joint on the vibration level of the ground surface highly depends on the load frequency. Highlights: To present a numerical model for the calculation of dynamic response of a segmented tunnel in the saturated soil. To analyze the influence of the tunnel joint on the soil stress and pore-water pressure of the foundation soil. To analyze the influence of the tunnel joint on the vibration of the ground surface.